Clinical and radiographic comparison of platelet-rich fibrin and mineral trioxide aggregate as pulpotomy agents in primary molars - Surendra Patidar; Namita Kalra; Amit Khatri; Rishi Tyagi (Wolters Kluwer Medknow Publications, 2017)
Aim: This study aimed to evaluate and compare the Platelet-rich fibrin (PRF) and Mineral trioxide aggregate (MTA) as a pulpotomy agent in primary molars. Material and Methods: In this study, 50 primary molars from 50 healthy children aged 5-9 years requiring pulpotomy were randomly allocated into two groups. In PRF group, after coronal pulp removal and hemostasis, remaining pulp tissue was covered with PRF preparation. In the MTA group, the pulp stumps were covered with MTA (Pro Root MTA-Root Canal Repair Material, Dentsply International Inc.) paste obtained by mixing MTA powder with sterile water at a 3:1 powder to water ratio. All teeth were restored with reinforced zinc oxide eugenol base and glass - ionomer cement. Stainless steel crowns were given in both groups 24 h after treatment. Clinical evaluation was undertaken at 1, 3, and 6 months intervals whereas radiographic evaluation of the treated teeth was carried out at the interval of 6 months. Results: By the end of 6 months, the overall success rate was 90% in PRF group and 92% in MTA Group. A statistically significant difference was observed between the groups at 6 months of follow-up (P < 0.05). The results were statistically nonsignificant between the groups (P > 0.05). Conclusion: Radiographic and clinical outcome in PRF group could suggest it as an acceptable alternative in pulpotomy of primary teeth. PRF holds a promising future in the area of primary tooth vital pulp therapy.